BRAIN, EMOTION, AND MORAL JUDGEMENT - Fransisca Ting (Buletin Psikologi, 2010)
The dual process theory posits that people relies on their emotion (especially negative emotions) when they are faced with personal moral dilemmas, such as pushing a person off a footbridge in order to stop a trolley that would otherwise kill five people. In an fMRI investigation, the medial frontal gyrus, posterior cingulate gyrus, and bilateral angular gyrus are more activated in considering a personal moral dilemma, leading them to make a characteristically deontological judgment. On the other hand, people are less emotionally engaged in non‐personal moral dilemmas, leading them to be more consequentialist in their judgment. Empathy is argued to be a salient moral emotion that could alter one’s moral judgment in moral dilemmas. Specifically, when judging about the permissibility of a person’s proposed action, the subjects will judge those they empathize with less harshly, and when they themselves have to make the decision, they will tend to save the party they empathize with across dilemmas.